Peran Hukum Islam dalam Mencegah Kekerasan Berbasis Rumah Tangga - Eni Silviyani (LPPM Universitas Al-Khairiyah, 2025)
This study examines the role of Islamic Law in preventing domestic violence (DV) through a comprehensive library-based analysis of classical and contemporary fiqh texts, national regulations, and recent scholarly publications. The findings indicate that fundamental principles of Islamic Law—such as justice, compassion, and the protection of life and dignity—serve as strong normative foundations for preventing domestic violence within Muslim families. However, the effectiveness of these principles depends significantly on contextual interpretation, adequate religious education, and institutional support, including premarital counseling and gender-sensitive mediation in Religious Courts. The maqāṣid al-sharī‘ah framework proves highly relevant, emphasizing the protection of family welfare and safety as core objectives of Islamic Law. This study concludes that preventing domestic violence requires synergy between humanistic Islamic teachings, responsive public policies, and community empowerment. The research contributes to strengthening domestic violence prevention efforts through an Islamic legal perspective that promotes justice and family well-being.